The Impact Of Job Stress, Work Discipline, And Job Satisfaction On Employee Performance At PT. Az.Ko: Dampak Stres Kerja, Disiplin Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan di PT. Az.Ko - Firman Setiabudi; Danang Aziz Akbarona; Junengsih (Jurnal Bisnis dan Ekonomi, 2026)
Objective : This study aims to analyze the influence of Job Stress, Work Discipline, and Job Satisfaction on Employee Performance at the Inbound Department of PT. AZ.KO in Cikarang. The research is driven by a consistent decline in container receiving target achievement from 2021 to 2024, indicating human resource performance issues amidst an operational target increase from 6,000 to 8,000 units. Methodology : Using a quantitative approach with descriptive and causal designs, the study surveyed all 60 employees of the Inbound Department using saturated sampling. Data were analyzed through multiple linear regression via SPSS. Research results : The results show that Job Stress, Work Discipline, and Job Satisfaction simultaneously have a significant effect on Employee Performance (R^2 = 68.2%). Partially, Job Stress has a significant negative effect, while Work Discipline and Job Satisfaction have significant positive effects. Management is advised to review workload distribution to mitigate stress while maintaining consistency in discipline and job satisfaction to achieve sustainable operational targets.